Isolated facial palsy due to intra-aural tick (ixodoidea) infestation - Asha'ari, Zamzil Amin; Abdullah, Baharudin; Hasan, Shahid; Sidek, Dinsuhaimi; Mat Jusoh, Noraffendie (Universiti Sains Malaysia, 2007)
A tick in the ear is a very painful condition and removal is difficult because it grips firmly to the external auditory canal or tympanicmembrane. Facial paralysis is a rarely reported localised neurological complication of an intra-aural tick infestation. The pathophysiology of localised paralysis is discussed, together with the safe way of handling patients with an intra-aural tick infestation